Effect of Cash Management on Financial Performance of Level Three and Four Public Hospitals in Meru County - Kimathi, Doreen Kanana; Kambura, Susan; Rintari, Nancy (International Journal of Professional Practice, 2024)
The Level three and four public hospitals focus on the provision of healthcare activities based on the recommendations of MOH. The financial success of hospitals is critical to the economic development of the country because it improves the quality of life, which in turn promotes economic growth by reducing poverty. The purpose of this study was to ascertain the effect of cash management on financial performance of Level three and Four Hospitals in Meru County. The study was grounded on the cash conversion cycle theory. Descriptive survey design, which allowed the researcher to explain the variables of the study was adopted. The target population comprised fifty-three officers from all the surveyed fifty-three Level three and four Hospitals in Meru County. Questionnaires were utilized. Census method was adopted to enlist all the 53 healthcare officers. Data was analyzed using SPSS version 29. Both descriptive and inferential statistics were used in analyzing data, and results displayed in tables and explanations. Regression analysis was utilized to determine the association between the variables. The study found out a statistically significant (p<0.05) and positive correlation coefficient of 0.820, signifying that cash management techniques impacted the financial performance of Meru County's Level Three and Four Hospitals. Additionally, the study found out that gross profit had a mean of 4.6 and standard deviation of 0.647; a net profit of 3.72, and a standard deviation of 1.02; and ROA of 3.32 and standard deviation of 1.335. The study concluded that the high expenditures that the hospitals incur affects the distribution of financial resources. Thus, the study recommends immediate policy intervention measures from the management to ensure that institutional financial resources are appropriately used, and more revenue sourcing channels are developed. This would ensure that the hospital has enough revenue to cater for the expenditures.